2015
DOI: 10.1177/0022022115588951
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Ethnic Identity as Predictors of Substance Use and Delinquency Among Immigrant Adolescents From the FSU and Ethiopia in Israel

Abstract: The current study explores perceived discrimination and ethnic identity as predictors of delinquency and substance use among adolescent immigrants in Israel. Theoretically, the study draws from strain theory, immigration-related theories of ethnic identity formation in adolescence, bi-dimensional theories of acculturation, and the rejection-identification model. The study involved 250 adolescents, 140 from the Former Soviet Union (FSU) and 110 from Ethiopia, aged 15 to 18 years (M = 16.7 years). Adolescents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 138 publications
(176 reference statements)
0
34
3
Order By: Relevance
“…In New Zealand, a study found that discrimination was associated with risky behaviors, and poorer health and health outcomes (Harris et al, ). Several studies on immigrant youth report discrimination from peers and teachers at school (Walsh, Fogel‐Grinvald, & Shneider, ; Zlotnick, Goldblatt, Shadmi, Birenbaum‐Carmeli, & Taychaw, ), at community organizations, and at health care sites (Zlotnick et al, ). Increasingly, however, evidence demonstrates that the effects of racism extend beyond school and neighborhood boundaries (Astell‐Burt, Maynard, Lenguerrand, & Harding, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand, a study found that discrimination was associated with risky behaviors, and poorer health and health outcomes (Harris et al, ). Several studies on immigrant youth report discrimination from peers and teachers at school (Walsh, Fogel‐Grinvald, & Shneider, ; Zlotnick, Goldblatt, Shadmi, Birenbaum‐Carmeli, & Taychaw, ), at community organizations, and at health care sites (Zlotnick et al, ). Increasingly, however, evidence demonstrates that the effects of racism extend beyond school and neighborhood boundaries (Astell‐Burt, Maynard, Lenguerrand, & Harding, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent statistics show that Ethiopian immigrants comprise about 1% of the total Israeli population, while Russian‐speaking immigrants comprise almost 15% (CBS‐Central Bureau of Statistics‐Israel, ). Existing studies suggest that both Russian and Ethiopian youth in Israel have experienced racism and suffered from discrimination in school and in Israeli society (Walsh et al, ; Zlotnick et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sellin's (1938) theory on culture, conflict, and crime led the way to much documentation on the connection between immigration and crime. This theory has been presented repeatedly over the years, mainly concerning second-generation youth, and especially in the wake of globalization (Anisef and Kilbride 2003;Freilich et al 2002;Marshall 1997;Schwartz et al 2015;Sellin 1938;Tonry 1997;Walsh, Fogel-Grinvald, and Schneider 2015).…”
Section: Juvenile Delinquencymentioning
confidence: 96%
“…Among some immigrant youth, these problems and difficulties express themselves in juvenile delinquency (Anisef and Kilbride 2003;Freilich et al 2002;Marshall 1997;Sellin 1938;Tonry 1997;Walsh et al 2015). Although this paper deals with immigrant youth, we should keep in mind that they are only a small percentage of all delinquent youth.…”
Section: Juvenile Delinquency Among Immigrantsmentioning
confidence: 99%
See 1 more Smart Citation